Understanding policy volatility in Sudan - El-Harizi, Khalid; Zaki, El Sayed; Prato, Bettina; Shields, Ghada (International Food Policy Research Institute, 2007)
In this paper we present the findings of a qualitative investigation into some dimensions and implications of policy volatility in the realms of natural resource (NR) governance and devolution in contemporary Sudan, with particular reference to Greater Kordofan. Our goal is to map out some aspects of the interplay between volatility, disempowerment processes affecting both state agents and the rural population, and certain problems of governance that are characteristic but not unique to Sudan. In particular, we argue that volatility is a dimension of poor governance worthy of investigation in its own right, as it is a primary ingredient of what we may call a “self-disempowering state,” where adaptive learning in policy processes is impeded and successful devolution faces particularly complex obstacles. The policy domain that we consider for analysis includes laws, regulations and policies enacted under the label of “Decentralization, Land Allocation and Land Use,” as well as large development projects supporting the decentralization or devolution of NR management to local communities in the region.